INFLUENCE OF A COMPLEX OF FOOD SUPPLEMENTS ON THE CONDITION OF RETINAL NEURONS IN RATS - Yeroshenko, G.A.; Shevchenko, K.V.; Synenko, V.A.; Vesnina, L.E.; Zviaholska, I.M.; Tymoshenko, Yu.V.; Ischenko, V.I. (World of Medicine and Biology, 2025)
The paper presents data from a morphometric study of the diameter of neurocyte nuclei in the outer nuclear, inner nuclear, and ganglion layers of the retina under the combined action of food additives. It has been established that the effect of a complex of dietary supplements – sodium glutamate, sodium nitrite, and Ponceau 4R – causes a progressive decrease in the average diameter of retinal nerve cell nuclei due to a decrease in euchromatin volume, which indicates a decrease in cell activity. The combined effect of food additives leads to the development of oxidative stress, to which proteins, lipids, and DNA respond, the development of nonspecific inflammation, structural degradation, and the development of gliosis in response to damage. Thus, monosodium glutamate, sodium nitrite, and Ponceau 4R affect the function of the visual analyzer, primarily causing deterioration and once again confirming the need for strict quality control of domestic and foreign products.
Keywords: food additives; monosodium glutamate; sodium nitrite; Ponceau 4R; retina; eye; oxidative stress; rats